MANAJEMEN MUTU TERPADU DAN IMPLEMENTASINYA DALAM DUNIA PENDIDIKAN - ANA BINTARI; DAKIR DAKIR; MUSLIMAH MUSLIMAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The increasingly fierce competition that occurs among sellers of products and services requires each to be able to maintain and improve the quality of the products or services produced. The lack of understanding of an organization or company, whether owned by the government or private, on how to maintain public trust in the products it produces can be a crucial problem. The existence of management is very important for the sustainability of a company or organization,